KEANEKARAGAMAN JENIS KUPU-KUPU (RHOPALOCERA) DI KAWASAN KAMPUS UNIVERSITAS RIAU SEBAGAI SUMBER BELAJAR BIOLOGI DALAM BENTUK POSTER - Indah Sujanna; Suwondo Suwondo; Elya Febrita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Research has been carried out which aims to determine the types of butterflies in the Riau University campus area. The research was conducted at the mini stadium orchard, Fisip orchard and Faperta orchard in August-September 2022. Sampling was carried out using an insec net. Then the butterflies that were caught were put into temporary storage bottles to be identified. The results of the research on the diversity of butterfly species in the Riau University area were then developed into posters that were used as learning resources. The design of poster media was carried out at the Biology Education Binawidya Campus, FKIP, Riau University.Key Words: Diversity, Butterfly, Posters